Calculation theory and damage analysis on crack width of RC seismic-damaged columns. (December 2021) - Cheng, Shitao; He, Haoxiang; Lan, Bingji
Abstract: In the light of the shortcomings of the calculation method for the diagonal crack width, a new method based on the bond-slip theory is proposed. In view of it is difficult to measure the external load or to predict the crack width accurately in actual earthquake scenario, it is difficult to evaluate the damage degree of seismic-damage column, the width calculation method of transverse cracks and diagonal cracks based on the flexural deformation and shear deformation is established. On this basis, a method and process for calculating the maximum crack width based on the horizontal displacement of the seismic-damaged RC column is proposed, and the analytical solution of the damage index of the RC column based on the crack width is obtained. The analysis of an example proves that the new method can be used to accurately calculate the crack width based on the horizontal displacement of the RC column, and the dynamic evolution process of the crack width and its failure mode can be revealed. In addition, the example analysis also proves that the damage value of the RC column obtained from the analytical solution of the damage index is reasonable and credible. This study can provide strong support for the rapid assessment of the seismic-damaged RC columns.